Fluctuating Weakness in an 18-Month-Boy: Congenital Myasthenia - Banerjee, Arundhati; Senguttuvan, Gananamani; Reddy, Chaitanya; Saini, Arushi Gahlot (Journal of Pediatric Neurology, 2020)
In this article, we reported a case of an 18-month-old male child patient who presented with motor predominant delay in attaining developmental milestones and early onset fatiguable weakness with ptosis and ophthalmoparesis. This ptosis and ophthalmoparesis typically worsened with progression of the day. Examination showed proximal weakness with preserved muscle stretch reflexes. Electrophysiology showed characteristic decrement on repetitive nerve stimulation test that localized to disorders of the neuromuscular junction. Next-generation sequencing showed a pathogenic variant of CHRNE that was responsible for congenital myasthenic syndrome. Such variants show increased improvement with salbutamol in addition to anticholinesterase inhibitors. Hence, the patient was started on pyridostigmine, and the plan was to add on salbutamol on follow-up if optimal improvement does not occur.
Keywords: ptosis; diurnal variation; ophthalmoparesis; pyridostigmine; salbutamol